1986
DOI: 10.1590/s0004-282x1986000300008
|View full text |Cite
|
Sign up to set email alerts
|

Neuroesquistossomose

Abstract: The low incidence of mansoni schistosomiasis involving the nervous system calls our attention in a country where 12 million people carry the intestinal form of the disease. Also, during autopsies the incidence of the parasites eggs occurs three to four times more often than the cases diagnosed in life. Therefore, new investigations become necessary around endemic areas. The cerebrospinal fluid syndrome of the neuroschistosomiasis must be searched among patients from endemic areas who present neurological sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
8

Year Published

1988
1988
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 6 publications
0
11
0
8
Order By: Relevance
“…Por outro lado, é comprovada sua quase nula especificidade na caracterização das lesões, não sendo ainda capaz, de maneira consistente, de permitir distinguir se uma lesão é infecciosa, inflamatória, isquêmica, tumoral, edema ou gliose 29 . Apesar disso, pela sua alta sensibilidade, a RM tem sido de grande valor para o fortalecimento do diagnóstico clínico da EM 22,23,25,[29][30][31][32][33] , doença tipicamente inflamatória, em que a tomografia computadorizada apresenta com frequência resultados normais 17,19,20,22,23,32,34 . Nos 18 pacientes com EM aqui apresentados e de acordo com os resultados já referidos, a RM confirmou sua alta sensibilidade: demonstrou anormalidades em 88,8% dos casos.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Por outro lado, é comprovada sua quase nula especificidade na caracterização das lesões, não sendo ainda capaz, de maneira consistente, de permitir distinguir se uma lesão é infecciosa, inflamatória, isquêmica, tumoral, edema ou gliose 29 . Apesar disso, pela sua alta sensibilidade, a RM tem sido de grande valor para o fortalecimento do diagnóstico clínico da EM 22,23,25,[29][30][31][32][33] , doença tipicamente inflamatória, em que a tomografia computadorizada apresenta com frequência resultados normais 17,19,20,22,23,32,34 . Nos 18 pacientes com EM aqui apresentados e de acordo com os resultados já referidos, a RM confirmou sua alta sensibilidade: demonstrou anormalidades em 88,8% dos casos.…”
Section: Discussionunclassified
“…Estes resultados são semelhantes aos encontrados nos pacientes de Lechtenberg e Vaida 13 e Nazareth de Andrade 20 , já citados anteriormente.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Essas reações imunológicas desencadeiam proliferação astrocitária, pleomorfismo microglial, tumefação e necrose neuronal, desmielinização da substância branca, das vias piramidais cruzadas e de focos isolados no cordão anterior da medula. As toxinas liberadas pelo ovo ou pelo granuloma podem causar lesões onde não há presença de ovos 1 . Acredita-se que nesses casos a extensão da lesão neurológica esteja relacionada à intensidade da resposta do hospedeiro.…”
Section: Relato Do Casounclassified
“…Previous studies have reported an incidence of 5% to 6% of spinal cord schistosomiasis (SCS) among patients with non-traumatic or non-neoplastic myelopathy 5,6 . From post-mortem studies, it has been estimated that between 20% and 30% of patients with mansonic schistosomiasis have compromising of the nervous system and that the incidence of asymptomatic NS is 3 to 4 times higher the frequency of symptomatic NS [7][8][9] . Difficulties in recognizing NS have been described and attributed as one of the causal factors of the low frequency of diagnosis 10 .…”
mentioning
confidence: 99%